RETRACTED: Simulation modeling of a synergetic chemical reactor control system - Siddikov Isamidin; Mamasodikov Yusufjon; Mamasodikova Nodira; Jurayeva Gulnozaxon (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001